Fallow Weed Control with Preemergence Applications of Balance Pro, Corvus, Banvel, Atrazine, and Authority MTZ - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Atrazine alone applied in the fall was less effective for kochia and Russian thistle control than other fall- or spring-applied herbicides in early summer. In mid season, control of kochia and Russian thistle was 85% or less with all fall-applied herbicides. Banvel (dicamba) increased kochia control when added to Balance Pro (isoxaflutole), plus Autumn Super (iodosulfuron + thiencarbazone), plus atrazine applied in the spring at mid season. All other spring herbicides were similar for kochia control. Russian thistle control was similar among all spring-applied herbicides except atrazine plus Banvel.
Keywords: Fallow; weed control; preemergence applications; kochia; Russian thistle; spring-applied herbicides; Balance Pro; Isoxaflutole; Corvus; Thiencarbazone; Banvel; Dicamba; atrazine; Authority MTZ; Sulfentrazone; Metribuzin